IMPACT OF BIO-FERTILIZER SEED TREATMENT ON SEED AND SEEDLING PARAMETERS OF MAIZE (ZEA MAYS L.) - PATHAK, ANIMESH; S. K. CHAKRABORTI (The Bioscan, 2014)
To study influence of inorganic nitrogen and seed treatment with Azospirillum on different seed quality parameters, four local cultivars of maize seed were treated with full inorganic nitrogen (T1), half inorganic nitrogen with Azospirillum (T2) and Azospirillum (T3). Germination percentage for T2 exhibited significant increase than T1 and T3. The fresh and dry weight of root and shoot was significantly high for T2 followed by T1 and than T3. The vigour index was also found to be significantly high in T2. When varieties were taken into account with regard to their response towards different treatments, V3 responded best followed by V2 and V1 for the character germination percentage. Increased germination percentage, vigour index by treatment T2 for different varieties of maize encourage use of low cost, ecofriendly Azospirillum seed treatment.